Turbulence of internal gravity waves in the laboratory - Cortet, Pierre-Philippe; Lanchon, Nicolas (Comptes Rendus. Physique)
In this article, we review the recent efforts of several teams that aimed at observing in the laboratory a turbulence of internal gravity waves in a density stratified fluid in the weakly non-linear regime. The common feature to these studies is that they adopted the same strategy of injecting energy in weakly non-linear waves before increasing the forcing amplitude in order to trigger a transition to a wave turbulence regime. The motivation to these works is twofold. On the one hand, it has long been proposed that the dynamics of small oceanic scales is driven by a regime of weakly non-linear internal wave turbulence, without however a definitive confirmation so far. A better understanding of the weakly non-linear internal wave turbulence thus appears as an important lever for improving the parameterization of small oceanic scales in climate models. On the other hand, the identification of valid solutions to the theory of internal gravity wave turbulence is still an open problem, and the experimental observation of this regime is therefore of great interest to guide future theoretical developments. We conclude that two features should be improved in the experiments in order to access to a genuine weakly non-linear wave turbulence in the laboratory. First, one should mitigate the finite size effects and especially prevent the concentration of the energy in wave eigenmodes of the fluid domain. Second, one should implement a significant increase of the wavelength at which the energy is injected in order to access to larger Reynolds numbers and lower flow Froude numbers and build a turbulence with well developed power law spectra while remaining in the weakly non-linear regime.